Plants used as fuel in the Arribes del Duero Natural Park (Salamanca-Zamora, Spain) - González, José Antonio; García-Barriuso, Mónica; Ramírez-Rodríguez, Rubén; Bernardos, Sonia; Amich, Francisco (Botanica Complutensis, 2013)
In the present work we document and analyze traditional knowledge relating to the use of different plants as fuel and lighting, as wood burned for different purposes (hearths, ovens, etc) and for the elaboration of charcoal by the inhabitants of the Arribes del Duero area (Salamanca-Zamora, Spain). We interviewed 80 informants (44 men and 36 women, with a mean age range of 72 (from 45 to 98) who use or who have recently used 39 vascular plants (including 19 botanical families) as fuel. In all cases those plants were exploited in a sustainable way. We performed the calculations necessary to unveil the cultural importance (CI) of each species. The most important taxa were Quercus ilex L. subsp. ballota (Desf.) Samp. (CI = 0.90) and Cytisus multiflorus (L’Hér.) Sweet (CI = 0.84).